(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2025)
Climate change poses increasing risks to natural ecosystems, water and land resources, and biodiversity, thereby underscoring the urgent need for strengthened legal mechanisms aimed at environmental protection and sustainable development. This article examines the improvement of legal criteria for protecting natural resources under the impact of climate change, focusing on the enhancement of national legislation, integration of international environmental norms, and the implementation of preventive, restorative, and adaptive legal measures. The research reveals that the effective governance of natural resources requires a comprehensive legal framework that incorporates climate resilience, environmental monitoring, public participation, and state accountability. The study highlights major legal challenges such as insufficient enforcement, fragmented regulatory mechanisms, and lack of climate-oriented legal expertise. Additionally, the article emphasizes the necessity of harmonizing national environmental laws with global standards, enhancing institutional capacity for environmental governance, and introducing innovative regulatory tools to ensure long-term preservation of natural resources. The findings provide strategic solutions to improve environmental legislation and strengthen legal protection policies against climate-induced resource degradation.